2022
DOI: 10.1021/acsabm.2c00228
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant-Free Green Synthesis of Au@Chlorophyll Nanorods for NIR PDT-Elicited CDT in Bladder Cancer Therapy

Abstract: The facile and straightforward fabrication of NIR-responsive theranostic materials with high biocompatibility is still an unmet need for nanomedicine applications. Here, we used a natural photosensitizer, iron chlorophyll (Chl/Fe), for the J-aggregate template-assisted synthesis of Au@Chl/Fe nanorods with high stability. The assembly of a high amount of Chl/Fe J-aggregate onto the Au surface enabled red–NIR fluorescence for monitoring and tracking residential tumor lesions. The Chl/Fe moieties condensed on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 69 publications
0
15
0
Order By: Relevance
“…Facing the clinical challenge of CDT, scientists prefer utilizing CDT combined with other therapies, such as PTT or PDT, to apply to bladder cancer. Liao et al presented a CDT-based approach combined with photodynamic therapy (PDT) in which PDT excites CDT in the NIR region to treat bladder cancer (Figure 14a) [129]. The photosensitizer Au@Chl/Fe-CPBA (Chl/Fe for iron chlorophyll and carboxyphenylboronic for CPBA) reduces toxicity and avoids it from entering into systemic circulation by an intravesical instillation [129] belonging to the iron-based inorganic material.…”
Section: Chemodynamic Therapy Of Bladder Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Facing the clinical challenge of CDT, scientists prefer utilizing CDT combined with other therapies, such as PTT or PDT, to apply to bladder cancer. Liao et al presented a CDT-based approach combined with photodynamic therapy (PDT) in which PDT excites CDT in the NIR region to treat bladder cancer (Figure 14a) [129]. The photosensitizer Au@Chl/Fe-CPBA (Chl/Fe for iron chlorophyll and carboxyphenylboronic for CPBA) reduces toxicity and avoids it from entering into systemic circulation by an intravesical instillation [129] belonging to the iron-based inorganic material.…”
Section: Chemodynamic Therapy Of Bladder Cancermentioning
confidence: 99%
“…Liao et al presented a CDT-based approach combined with photodynamic therapy (PDT) in which PDT excites CDT in the NIR region to treat bladder cancer (Figure 14a) [129]. The photosensitizer Au@Chl/Fe-CPBA (Chl/Fe for iron chlorophyll and carboxyphenylboronic for CPBA) reduces toxicity and avoids it from entering into systemic circulation by an intravesical instillation [129] belonging to the iron-based inorganic material. As demonstrated in Figure 14a, the experiment illustrates that the direct NIR light-induced PDT, before a lengthy CDT period, accelerates the conversion by ferrous ions in the tumor microenvironment from H 2 O 2 to O 2 and •OH, which exacerbates the inhibition of the growth of bladder cancer cells, resulting in the immediate consumption of the glutathione (GSH) antioxidant molecules and the triggering of membrane lipid peroxidation [129].…”
Section: Chemodynamic Therapy Of Bladder Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of nano drugs have been reported to specifically adhere to bladder cancer cells and deliver iron through endocytosis when exposed to laser irradiation, resulting in ROS generation and accumulation and subsequent GSH and GPX4 depletion, ultimately leading to ferroptosis ( Liao et al, 2022 ). Another approach is to enhance photodynamic therapy (PDT)-chemodynamic therapy (CDT) sensitivity and induce toxicity ( Chin et al, 2022 ; Liao et al, 2022 ). AuNRs&IONs@Gel is a gel delivery platform with embedded gold nanorods (AuNRs) and iron oxide nanoparticles (IONs).…”
Section: Potential Therapeutic Drugsmentioning
confidence: 99%
“…Conversely, nanomaterials with passive and active target abilities can enhance accumulation at the tumor site and reduce adverse effects 14 . For example, Liao et al reported a nanodrug that specifically targets BCa cells to deliver iron ions, produce excess ROS, and ultimately lead to ferroptosis 15 . Moreover, AuNRs, IONs@Gel, 16 and gold clusters (PAA4 and PAA5) 17 have also been reported have potential for BCa treatment targeting the ferroptosis pathway.…”
Section: Introductionmentioning
confidence: 99%